Clima urbano: um estudo aplicado a Belo Horizonte, MG - Rubia Cecilia Augusta Franscisco (2012)
This work aim at analyzing the influence of the urban form and land use in the local climate using climate monitoring and numerical simulation through the microclimatic model ENVI-Met©. A selected area in the city of Belo Horizonte, Brazil, was taken as case study. This area is located at the Northern region of Belo Horizonte, in the Planalto district, considered as a region for increasing the density and land occupation. Points for climate monitoring were set within a local green park (the city park Lagoa do Nado) and in its surrounding urban area in order to compare the thermo-hygrometric behavior of green and constructed areas. Data of air temperature, relative humidity, wind speed and direction were collected by a meteorological tower near the area and served as input and calibration for the ENVI-Met© model. Data of air temperature and relative humidity registered by the digital thermo-hygrometers set within and around the park served as references for comparison with the model results. The methodology was developed for observing the local thermal environment applying the simulation methods in architecture and urban planning: the calibrated case study area was compared to two hypothetical scenarios with changes in land use. One of them corresponds to increasing the heights of buildings and the other scenario replaced the arboreal vegetation of the Park Lagoa do Nado for grass. As a result, different microclimatic conditions were observed in the two hypothetical scenarios when compared to the calibrated case study. This clearly showed that urban design can produce diverse microclimatic conditions. Field monitoring helped to identify different climatic characteristics within green and built areas, becoming reference to the process of calibrating the micrometeorological model. This methodology may be used by planners in order to test design solutions and to preserve better quality of urban thermal comfort. Keywords: urban climate, numerical simulation, urban planning.